Convalescent plasma a tool to treat or a reason to retreat in COVID-19 infection: a systematic review and meta-analysis - Kundal, Raksha; Kant, Vishal; Kundal, Vijay K.; Pandey, Maitree; Goel, Manish; Basnotra, Ritika (International Journal of Research in Medical Sciences, 2022)
For management of Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection, different therapeutic approaches are being given for mitigating symptoms that reduce hospital and intensive care unit (ICU) stay and decreasing the mortality. Convalescent plasma therapy is among one of the therapeutic approaches and to determine its effect on COVID-19, we aggregated patient outcome data from 8 randomized clinical trials (RCT). Studies published between 01 January 2020 to 28 February 2021 were identified via a thorough systematic search of PubMed, Embase, Medline and preprint platforms MedRxiv databases and data was analysed for its efficacy. Random-effects analyses of RCT demonstrated that COVID-19 patients who received convalescent plasma therapy along with standard of care showed a similar mortality rate when compared to patients receiving only standard of care treatments. Additional data showed that these data doesn’t provide evidence favoring the efficacy of human convalescent plasma as a therapeutic agent in hospitalized COVID-19 patients.